Neuroligin 2 deletion alters inhibitory synapse function and anxiety-associated neuronal activation in the amygdala. (January 2016) - Babaev, Olga; Botta, Paolo; Meyer, Elisabeth; Müller, Christian; Ehrenreich, Hannelore; Brose, Nils; Lüthi, Andreas; Krueger-Burg, Dilja
Abstract: Neuroligin 2 (Nlgn2) is a synaptic adhesion protein that plays a central role in the maturation and function of inhibitory synapses. Nlgn2 mutations have been associated with psychiatric disorders such as schizophrenia, and in mice, deletion of Nlgn2 results in a pronounced anxiety phenotype. To date, however, the molecular and cellular mechanisms linking Nlgn2 deletion to psychiatric phenotypes remain completely unknown. The aim of this study was therefore to define the role of Nlgn2 in anxiety-related neural circuits. To this end, we used a combination of behavioral, immunohistochemical, and electrophysiological approaches in Nlgn2 knockout (KO) mice to expand the behavioral characterization of these mice and to assess the functional consequences of Nlgn2 deletion in the amygdala. Moreover, we investigated the differential activation of anxiety-related circuits in Nlgn2 KO mice using a cFOS activation assay following exposure to an anxiogenic stimulus. We found that Nlgn2 is present at the majority of inhibitory synapses in the basal amygdala, where its deletion affects postsynaptic structures specifically at perisomatic sites and leads to impaired inhibitory synaptic transmission. Following exposure to an anxiogenic environment, Nlgn2 KO mice show a robust anxiety phenotype as well as exacerbated induction of cFOS expression specifically in CaMKII-positive projection neurons, but not in parvalbumin- or somatostatin-positive interneurons. Our data indicate that Nlgn2 deletion predominantly affects inhibitory synapses onto projection neurons in basal amygdala, resulting in decreased inhibitory drive onto these neurons and leading to their excessive activation under anxiogenic conditions. This article is part of the Special Issue entitled 'Synaptopathy – from Biology to Therapy'. Highlights: Nlgn2 is localized to inhibitory synapses in mouse basal amygdala. Perisomatic inhibitory postsynapses are altered in Nlgn2 knockout mouse amygdala. Inhibitory synaptic transmission is impaired in Nlgn2 knockout mouse amygdala. Nlgn2 knockout mice show a robust anxiety phenotype. Induction of cFos under anxiogenic conditions is exaggerated in Nlgn2 knockout mice.